2022
DOI: 10.3390/vaccines10081189
|View full text |Cite
|
Sign up to set email alerts
|

Humoral and Cellular Immunogenicity of Six Different Vaccines against SARS-CoV-2 in Adults: A Comparative Study in Tunisia (North Africa)

Abstract: Background: The mass vaccination campaign against SARS-CoV-2 was started in Tunisia on 13 March 2021 by using progressively seven different vaccines approved for emergency use. Herein, we aimed to evaluate the humoral and cellular immunity in subjects aged 40 years and over who received one of the following two-dose regimen vaccines against SARS-CoV-2, namely mRNA-1273 or Spikevax (Moderna), BNT162B2 or Comirnaty (Pfizer-BioNTech), Gam-COVID-Vac or Sputnik V (Gamaleya Research Institute), ChAdOx1-S or Vaxzevri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…RNA vaccines have been shown to induce the highest levels of humoral and cellular anti-S responses, followed by adenovirus vaccines and then inactivated vaccines. A previous study found better humoral and cellular immunogenicity for RNA-based COVID-19 vaccines including BNT162b2 [29] . Dashdorj et al.…”
Section: Discussionmentioning
confidence: 90%
“…RNA vaccines have been shown to induce the highest levels of humoral and cellular anti-S responses, followed by adenovirus vaccines and then inactivated vaccines. A previous study found better humoral and cellular immunogenicity for RNA-based COVID-19 vaccines including BNT162b2 [29] . Dashdorj et al.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, mRNA COVID‐19 vaccines have been demonstrated to elicit superior adaptive cellular responses compared to other authorized COVID‐19 vaccines. Median levels of CD4 + responses following two doses of mRNA vaccine were 3–4‐fold higher than in the case of two doses of adenoviral AZD1222 vaccine (Oxford/AstraZeneca), 5–6‐fold higher compared to two doses of adenoviral Sputnik V vaccine (Gamaleya Research Institute, Russia), and over 10‐fold higher than after administration of two doses of inactivated CoronaVac (Sinovac) and BIBP (Sinopharm) vaccines 63 . The CD8 + reactivity was also significantly higher after mRNA vaccine administration than in the case of other formulations 63 .…”
Section: Advantages Of Mrna Vaccinesmentioning
confidence: 87%
“…The participants involved were mostly of a younger age, predominantly female, and had either not been infected (no symptoms) or mild manifestations of COVID-19 during prior infections. A recent study reported that vaccines from the same platforms had elicited similar rates of specific anti-S antibodies [ 23 , 38 ]. Moreover, the numbers in the different vaccine groups had been low except in the RNA vaccine group.…”
Section: Discussionmentioning
confidence: 99%